Solid-state electrolyte surface coating, method of preparation and use

CN122968464APending Publication Date: 2026-10-23NANJING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510474339.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,锂金属修饰对操作环境和操作者要求高;合金负极,工作电位相对锂金属更高,虽然能提升对硫化物电解质稳定性,但电池比能量也会相应降低;新型电解质设计,需要大量的前期投入,且会对现有产线提出新要求,耗时长

Benefits of technology

[0017]有益效果:(1)本发明通过机械球磨的方式使得有机锂盐和固态电解质发生反应,生成含Li2S、LiBO2、LiF、LixPOyFz等无机物及有机物B-C、C-S、C-F化物的包覆层,相较于简单的物理混合反应,本发明的包覆层结构更为稳定且兼容性更好;(2)所述包覆层能抑制电解质与锂金属之间的副反应,提升稳定锂金属/电解质界面稳定性,降低副产物的产生,减少锂金属和电解质界面处枝晶生长;(3)由于无机/有机包覆层的存在,所得的固态电解质电子电导率降低,能降低锂在电解质层中直接成核风险,从而减少电解质层内枝晶。(4)所述包覆层构建的全固态锂金属电池,能实现了高循环稳定性和高比能电池的目标。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968464A_ABST
    Figure CN122968464A_ABST
Patent Text Reader

Abstract

This invention discloses a solid electrolyte surface coating layer, its preparation method, and its application. In an inert atmosphere, an organic lithium salt is added to an inorganic solid electrolyte, and the mixture is mechanically ball-milled and reacted to obtain the solid electrolyte surface coating layer. The advantages are: (1) This invention uses mechanical ball milling to allow the organic lithium salt and the solid electrolyte to react, generating a coating layer containing Li2S, LiBO2, LiF, and Li... x PO y F z The coating layer of inorganic and organic compounds such as B-C, C-F, and C-S has a more stable structure and better compatibility than simple physical mixing reactions; (2) The coating layer can suppress side reactions between the electrolyte and lithium metal and reduce the electronic conductivity of the electrolyte, thereby improving the stability of the lithium metal / electrolyte interface, reducing the generation of by-products, and suppressing dendrite growth; (3) The all-solid-state lithium metal battery constructed by the coating layer can achieve the goal of high cycle stability and high specific energy battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of all-solid-state battery technology, and relates to the modification of solid electrolytes in all-solid-state batteries, specifically the solid electrolyte surface coating layer, preparation method and application. Background Technology

[0002] Although lithium batteries are widely used, the use of flammable and volatile electrolytes in traditional liquid batteries has left many safety hazards. Therefore, all-solid-state batteries using non-flammable solid powders have received widespread attention due to their reduced potential safety risks.

[0003] Among many inorganic solid electrolytes, sulfide electrolytes are distinguished by their high ionic conductivity (~10). -3 Its advantages, such as low S / cm, low Young's modulus, and ease of molding, make it stand out. However, sulfide electrolytes have a narrow electrochemical window and exhibit significant (e)chemical side reactions with lithium metal. At the lithium metal-electrolyte interface, reduction reactions occur, generating unevenly distributed byproducts with low ionic conductivity, leading to uneven lithium deposition. Furthermore, sulfide electrolytes have high electronic conductivity, allowing lithium ions to be directly reduced at the electrolyte grain boundaries, resulting in lithium dendrites and ultimately causing a short circuit in the battery.

[0004] Existing modification methods include lithium metal modification, alloy anode application, and novel electrolyte synthesis. However, lithium metal modification places high demands on the operating environment and operators; alloy anodes, with their higher operating potential compared to lithium metal, improve stability against sulfide electrolytes, but consequently reduce battery specific energy; and novel electrolyte design requires significant upfront investment, imposes new requirements on existing production lines, and is time-consuming. Therefore, finding a simple method to process existing electrolytes can effectively accelerate the development of all-solid-state lithium metal batteries.

[0005] For example, Chinese patent CN107452983B discloses a lithium-ion battery composite electrolyte, its preparation method, and a lithium-ion battery, which involves coating organic lithium salts on the surface of sulfide solid electrolyte particles and / or filling them in the gaps between the particles. The design concept of this prior art is to utilize the plastic deformation property of organic lithium salts to promote their coating on the surface of the solid electrolyte or filling of the particle gaps during ball milling, thereby reducing the interfacial influence between inorganic solid electrolyte particles and between the electrolyte and the positive and negative electrodes. The technical effect achieved by this prior art is that, after the above physical coating or filling, the ionic conductivity of the solid electrolyte is greatly improved, resulting in better cycle performance. Summary of the Invention

[0006] Technical Problem Solved: To overcome the shortcomings of existing technologies, this invention achieves a coating layer by ball milling organic lithium salt and solid electrolyte to induce a chemical reaction. This coating layer results in high compatibility between the solid electrolyte and lithium metal, effectively stabilizing the lithium metal anode / electrolyte interface, and thus realizing a long-cycle-stable all-solid-state lithium metal battery. Therefore, this invention provides a solid electrolyte surface coating layer, its preparation method, and its applications.

[0007] Technical solution: A method for preparing a surface coating layer of a solid electrolyte, wherein the method comprises: adding an organic lithium salt to an inorganic solid electrolyte in an inert atmosphere, mechanically ball milling and mixing, and reacting to obtain a surface coating layer of the solid electrolyte (or a surface-coated modified solid electrolyte).

[0008] Preferably, the mass ratio of organic lithium salt to inorganic solid electrolyte is 0.005-0.05:1.

[0009] Preferably, the organic lithium salt includes: lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(trifluoromethanesulfonyl)imide, or lithium bis(fluorosulfonyl)imide; the inorganic solid electrolyte includes: Li 5.5 PS 4.5 Cl 1.5 , Li6PS5Cl, Li6PS5Br, 75Li2S·25P2S5, Li7P3S 11 Li 10 GeP2S 12 Or Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 .

[0010] Preferably, the mechanical ball mill is a planetary mechanical ball mill, in which the mass ratio of the milling beads to the mixture of organic lithium salt and inorganic solid electrolyte is 10-100:1, the rotation speed is 100-600 rpm, and the time is 3-24 hours.

[0011] The solid electrolyte surface coating layer prepared by any of the methods described above is characterized in that the coating layer comprises inorganic substances Li₂S, LiBO₂, LiF, and Li x PO y F z At least one of the organic compounds BC, CS, and CF.

[0012] Preferably, the outer layer of the coating is an inorganic / organic composite layer, and the inner layer is an inorganic-rich layer.

[0013] The above-described coating layers are used to reduce the electronic conductivity of solid electrolytes.

[0014] The above-described coating layer is used to suppress side reactions between the electrolyte and lithium metal and to reduce dendrite growth.

[0015] The above-described coating layers are used in the fabrication of all-solid-state lithium metal batteries.

[0016] Preferably, the all-solid-state lithium metal battery comprises: an all-solid-state composite positive electrode, a lithium metal negative electrode, and a solid electrolyte containing a coating layer; wherein, the all-solid-state composite positive electrode comprises an active material, a carbon material, and solid electrolyte powder; the active material is LiNi. x Mn y Co 1-x-y O2(0<x<1, 0<y<1), LiNi x Mn y Al 1-x-y O2 (0 < x < 1, 0 < y < 1) and LiCoO2; the carbon material is at least one of vapor-grown carbon fiber, acetylene black, Ketjen black, and carbon nanotubes; the solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 , Li6PS5Cl, Li6PS5Br, 75Li2S·25P2S5, Li7P3S 11 Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of them.

[0017] Beneficial effects: (1) This invention uses mechanical ball milling to react organic lithium salts and solid electrolytes to generate compounds containing Li2S, LiBO2, LiF, and Li x PO y F z (1) The coating layer of inorganic and organic compounds such as BC, CS, and CF compounds has a more stable structure and better compatibility than simple physical mixing reactions; (2) The coating layer can suppress side reactions between the electrolyte and lithium metal, improve the stability of the lithium metal / electrolyte interface, reduce the generation of by-products, and reduce dendrite growth at the lithium metal and electrolyte interface; (3) Due to the presence of the inorganic / organic coating layer, the electronic conductivity of the resulting solid electrolyte is reduced, which can reduce the risk of direct nucleation of lithium in the electrolyte layer, thereby reducing dendrites in the electrolyte layer; (4) The all-solid-state lithium metal battery constructed by the coating layer can achieve the goal of high cycle stability and high specific energy battery. Attached Figure Description

[0018] Figure 1The images show scanning electron microscope (a) and energy dispersive spectroscopy (EDS) spectra of the solid electrolyte prepared in Example 1.

[0019] Figure 2 This is the X-ray photoelectron spectrum of the solid electrolyte prepared in Example 1;

[0020] Figure 3 This is a time-of-flight secondary ion mass spectrometry analysis of the surface components of the solid electrolyte obtained in Example 1;

[0021] Figure 4 This is the electrochemical impedance spectroscopy of the solid electrolyte prepared in Example 1;

[0022] Figure 5 This is a graph showing the electronic conductivity of the solid electrolyte prepared in Example 1;

[0023] Figure 6 This is the electrochemical impedance spectroscopy of the solid electrolyte prepared in Example 2;

[0024] Figure 7 The solid electrolyte prepared in Example 1 was used in a lithium metal symmetric battery at 0.2 mA / cm². 2 The current density and 0.2 mAh / cm 2 Cyclic plot (a) under surface load; Plot of ultimate current density test results (b);

[0025] Figure 8 The solid electrolyte prepared in Example 1 was used in a lithium metal symmetric battery at 0.2 mA / cm². 2 The current density and 0.2 mAh / cm 2 X-ray photoelectron spectroscopy of the solid electrolyte interface composition between lithium metal and electrolyte after 1000 hours of cycling at the surface loading level.

[0026] Figure 9 The solid electrolyte prepared in Example 1 was used in a lithium metal symmetric battery at 0.2 mA / cm². 2 The current density and 0.2 mAh / cm 2 Time-of-flight secondary ion mass spectrometry analysis of the solid electrolyte interface composition between lithium metal and electrolyte after 1000 hours of cycling at the surface loading.

[0027] Figure 10 The graphs (a) and (b) show the 0.5C long-cycle performance of the solid electrolyte prepared in Example 2 in an all-solid-state ternary-lithium metal battery.

[0028] Figure 11 This is a graph showing the electronic conductivity of the solid electrolyte sheet in Example 1.

[0029] Figure 12 This is the charge / discharge curve of the all-solid-state battery in Comparison Example 2;

[0030] Figure 13 This is a simulation diagram of a solid electrolyte with the coating layer described in this invention and the uncoated case. Detailed Implementation

[0031] The following embodiments further illustrate the content of the present invention, but should not be construed as limiting the present invention. Modifications and substitutions made to the methods, steps, or conditions of the present invention without departing from the spirit and essence of the invention are all within the scope of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0032] Example 1

[0033] This embodiment uses lithium difluorooxalate borate to target Li 5.5 PS 4.5 Cl 1.5 The surface is coated, and the specific steps are as follows:

[0034] Step 1: In an argon-filled glove box with an oxygen level of less than 50 ppm, weigh out 500 mg of Li. 5.5 PS 4.5 Cl 1.5 Sulfide solid electrolyte powder and 5 mg of lithium difluorooxalate borate were placed in a zirconia ball mill jar, and then 50 g of 10 mm diameter zirconia grinding balls were added to the jar.

[0035] Step 2: After sealing the ball mill jar containing the sample, remove it from the glove box and thoroughly mix it in a planetary ball mill at 400 rpm. The ball mill operation program is set to first ball mill in the forward direction for 3 minutes, then rest for 2 minutes, then ball mill in the reverse direction for 3 minutes, and finally rest for 2 minutes. The total ball milling time is set to 600 minutes. Subsequently, the surface-coated electrolyte is obtained and stored in an argon-filled glove box.

[0036] Step 3: Surface composition analysis of the electrolyte powder was performed using X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry. The test results are as follows: Figure 2 and 3 As shown. Inorganic substances present on the electrolyte surface include: LiBO2, LiF, and Li. x PO y F z The organic matter consists mainly of BC compounds. Furthermore, the outer layer is an inorganic / organic composite layer, while the inner layer is primarily inorganic-rich.

[0037] Step 4: In an argon-filled glove box, weigh 100 mg of the surface-modified electrolyte prepared in this example, place it in a solid-state battery mold with a diameter of 10 mm, apply pressure of 300 MPa for 5 minutes using a tablet press, and then unmold to obtain a smooth and flat solid electrolyte sheet P1.

[0038] Step 5: Use a high-powered measuring device to test the ionic conductivity of electrolyte sheet P1. The test results are as follows: Figure 4 As shown, the ionic conductivity at 30℃ is 2.05 mS / cm.

[0039] Step 6: The electronic conductivity of electrolyte sheet P1 was tested using DC polarization, with the test bias voltage set to 0.5V. The test results are as follows: Figure 5 As shown, at 30℃, the electronic conductivity of the electrolyte is 2.7 × 10⁻⁶. -8 S / cm.

[0040] The surface-modified electrolyte prepared in this embodiment is used to prepare a lithium-lithium symmetric battery. The steps are as follows:

[0041] (1) Weigh 120 mg of the surface-modified electrolyte prepared in Example 1 and place it in a solid battery mold with a diameter of 10 mm. Press it with a tablet press at 300 MPa for 5 minutes to obtain a smooth and flat solid electrolyte layer.

[0042] (2) Cut flat lithium sheets with a diameter of 9 mm from a 50 μm thick lithium strip. Then take two cut lithium sheets and place them on both sides of the electrolyte sheet, and then place stainless steel foil current collectors with a diameter of 10 mm on each side.

[0043] (3) Place the battery mold on a stainless steel pressure mold, apply pressure at 10 MPa, and tighten the mold. After placing it in a 30℃ constant temperature chamber for 4 hours, perform the battery test. Figure 7 (a) This symmetrical cell operates at 0.2 mA / cm 2 The current density and 0.2 mA / cm 2 The lithium metal exhibits stable cycling performance exceeding 1200 hours at a surface loading capacity, demonstrating high compatibility between lithium metal and the surface-treated electrolyte. Figure 7 (b) shows the limiting current density test of this symmetrical cell. The results show a current density as high as 2.4 mA / cm². 2 The symmetrical battery can still operate stably, indicating that the modified electrolyte has good compatibility with lithium metal.

[0044] (4) For 0.2mA / cm 2 The current density and 0.2 mA / cm 2 X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry were used to analyze the lithium metal-electrolyte interface in a symmetric battery after 1000 hours of cycling at a certain surface loading capacity. The test results are as follows: Figure 8 and 9 As shown, the solid electrolyte interface layer at the lithium metal-electrolyte interface mainly includes Li₂S, LiBO₂, LiF, and Li x PO y F z It is composed of inorganic and some organic substances. In terms of distribution, the side closer to the lithium metal is mainly an inorganic / organic composite layer, while the side closer to the electrolyte is mainly an inorganic-rich layer.

[0045] Example 2

[0046] This embodiment uses lithium difluorooxalate borate and lithium bis(fluorosulfonyl)imide to target Li 5.5 PS 4.5 Cl 1.5 The surface is coated using the following steps:

[0047] Step 1: In an argon-filled glove box with an oxygen level of less than 50 ppm, weigh out 70 mg of lithium difluorooxalate borate and 30 mg of lithium difluorosulfonyl imide. Then, manually mix the two lithium salts in a mortar using a mortar stick for 10 minutes. Afterward, weigh out 500 mg of Li... 5.5 PS 4.5 Cl 1.5 Sulfide solid electrolyte powder and 10 mg of mixed lithium difluorooxalate borate and lithium difluorosulfonyl imide were placed in a zirconia ball mill jar, and then 40 g of 8 mm diameter zirconia ball milling beads were added to the jar.

[0048] Step 2: After sealing the ball mill jar containing the sample, remove it from the glove box and thoroughly mix it in a planetary ball mill at 300 rpm. The ball mill operation program is set to first ball mill in the forward direction for 2 minutes, then rest for 1 minute, then ball mill in the reverse direction for 2 minutes, and then rest for 1 minute. The total ball milling time is set to 1100 minutes. Subsequently, the surface-coated electrolyte is obtained and stored in an argon-filled glove box.

[0049] Step 3: In an argon-filled glove box, weigh 100 mg of the surface-modified electrolyte prepared in this example, place it in a solid-state battery mold with a diameter of 10 mm, apply pressure of 300 MPa for 5 minutes using a tablet press, and then unmold to obtain a smooth and flat solid electrolyte sheet P2.

[0050] Step 4: Use a high-powered measuring device to test the ionic conductivity of electrolyte sheet P2. The test results are as follows: Figure 6 As shown, the ionic conductivity at 30℃ is 0.82 mS / cm.

[0051] The surface-modified electrolyte prepared in this embodiment is used to prepare an all-solid-state ternary lithium metal battery. The steps are as follows:

[0052] (1) First, weigh 100mg of surface-modified electrolyte and place it in a solid battery mold with a diameter of 10mm. Then, press it at 300MPa for 5 minutes using a tablet press to obtain a smooth and flat solid electrolyte layer.

[0053] (2) Weigh 10 mg of LiNi prepared in Example 3 0.8 Mn 0.1 Co 0.1 An O2(NMC) composite positive electrode was uniformly spread on one side of the electrolyte sheet from step 1, followed by the placement of a 10mm diameter carbon-aluminum foil as the positive electrode current collector. The electrode was then pressurized at 400MPa for 3 minutes using a tablet press.

[0054] The NMC composite cathode was prepared by the following method: 70 mg of NMC and 30 mg of Li were weighed in an argon-filled glove box with an oxygen content of less than 50 ppm. 5.5 PS 4.5 Cl 1.5 The two materials were manually mixed in a mortar and pestle for 10 minutes. Then, 5 mg of Super P powder was added to the mixture, and they were mixed for 30 minutes. The resulting NMC composite cathode was stored in an argon-filled glove box.

[0055] (3) Cut a flat lithium sheet with a diameter of 9 mm from a 50 μm thick lithium strip. Then place it on the other side of the electrolyte sheet and place a 10 mm diameter stainless steel foil current collector.

[0056] All the above steps were completed in an argon-filled glove box with an oxygen level of less than 50 ppm.

[0057] (4) Place the battery mold on a stainless steel pressure mold, apply pressure at 20 MPa, and tighten the mold. After placing it in a 30℃ constant temperature chamber for 4 hours, perform a full-cell test. The first two cycle rates are 0.1C, and subsequent cycle rates are 0.5C. Figure 10 a. A fully solid-state lithium metal-NMC battery using lithium metal as the negative electrode and a surface-treated electrolyte as the intermediate electrolyte layer can achieve a first-cycle capacity of 143 mAh / g at 0.5C. NMC -1 After 200 cycles, the capacity retention rate was still 83.4%. Figure 10 b is the charge-discharge curve of the corresponding all-solid-state ternary lithium metal battery.

[0058] Compare with Example 1

[0059] This comparative example is for Li 5.5 PS 4.5 Cl 1.5 The electronic conductivity of the electrolyte was tested, and the steps and results are as follows:

[0060] Step 1: In an argon-filled glove box, weigh 100 mg of Li 5.5 PS 4.5 Cl 1.5 The electrolyte was placed in a solid-state battery mold with a diameter of 10 mm, and after applying pressure of 300 MPa for 5 minutes using a tablet press, the mold was removed to obtain a smooth and flat solid electrolyte sheet P3.

[0061] Step 2: The electronic conductivity of electrolyte sheet P3 was tested using DC polarization, with a test bias voltage set to 0.5V. The test results are as follows: Figure 11 As shown, at 30℃, the electronic conductivity of the electrolyte is 7.2 × 10⁻⁶. -8 S / cm.

[0062] Compare with Example 2

[0063] This comparative example uses Li 5.5 PS 4.5 Cl 1.5 The electrolyte preparation for an all-solid-state ternary lithium metal battery differs from Example 2 in that the intermediate electrolyte layer uses untreated Li₂. 5.5 PS 4.5 Cl 1.5 . Figure 12 This is the 0.5C cycle charge-discharge curve of the corresponding all-solid-state ternary lithium metal anode battery, where the first two cycles have a cycle rate of 0.1C. After 0.5C cycling, the battery experiences a severe short circuit on the fifth charge cycle.

Claims

1. A method for preparing a surface coating layer for a solid electrolyte, characterized in that, The method is as follows: In an inert atmosphere, an organic lithium salt is added to an inorganic solid electrolyte, and the mixture is mechanically ball-milled and reacted to obtain a solid electrolyte surface coating layer.

2. The method for preparing the solid electrolyte surface coating layer according to claim 1, characterized in that, The mass ratio of organic lithium salt to inorganic solid electrolyte is 0.005-0.05:

1.

3. The method for preparing the solid electrolyte surface coating layer according to claim 1, characterized in that, The organic lithium salt includes: lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(trifluoromethanesulfonyl)imide, or lithium bis(fluorosulfonyl)imide; the inorganic solid electrolyte includes: Li 5.5 PS 4.5 Cl 1.5 , Li6PS5Cl, Li6PS5Br, 75Li2S·25P2S5, Li7P3S 11 Li 10 GeP2S 12 Or Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 .

4. The method for preparing the solid electrolyte surface coating layer according to claim 1, characterized in that, The mechanical ball mill is a planetary mechanical ball mill. During the process, the mass ratio of the milling beads to the mixture of organic lithium salt and inorganic solid electrolyte is 10-100:1, the rotation speed is 100-600 rpm, and the time is 3-24 hours.

5. The solid electrolyte surface coating layer prepared by the method according to any one of claims 1-4, characterized in that, The coating layer includes inorganic substances such as Li₂S, LiBO₂, LiF, and Li. x PO y F z At least one of the organic compounds BC, CF, and CS.

6. The solid electrolyte surface coating layer according to claim 5, characterized in that, The outer layer of the coating is an inorganic / organic composite layer, and the inner layer is an inorganic-rich layer.

7. The application of the coating layer according to claim 5 in reducing the electronic conductivity of solid electrolytes.

8. The application of the coating layer of claim 5 in suppressing side reactions between the electrolyte and lithium metal and reducing dendrite growth.

9. The application of the coating layer according to claim 5 in the preparation of all-solid-state lithium metal batteries.

10. The application according to claim 9, characterized in that, The all-solid-state lithium metal battery comprises: an all-solid-state composite cathode, a lithium metal anode, and a solid electrolyte with a coating layer; wherein the all-solid-state composite cathode comprises an active material, a carbon material, and solid electrolyte powder; the active material is LiNi. x Mn y Co 1-x-y O2(0<x<1, 0<y<1), LiNi x Mn y Al 1-x-y O2 (0 < x < 1, 0 < y < 1) and LiCoO2; the carbon material is at least one of vapor-grown carbon fiber, acetylene black, Ketjen black, and carbon nanotubes; the solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 , Li6PS5Cl, Li6PS5Br, 75Li2S·25P2S5, Li7P3S 11 Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of them.

Citation Information

Patent Citations

  • A composite electrolyte for lithium-ion batteries, its preparation method, and lithium-ion batteries.

    CN107452983B